Business Process Design With BPR Life Cycle in Fertilizer Provision - Ghina Anggun; Farrikh Alzami; Mila Sartika; Sri Handayani; Jumanto; Rindra Yusianto; Firman Wahyudi (Universitas Medan Area, 2023)
Fertilizer is a supporter of soil growth and enrichment so as to increase agricultural production while at the same time improving environmental quality. The use of fertilizer is adjusted to the amount of land needed and the number of seeds purchased. In reality, fertilizer for shallots is still difficult to obtain, and prices are still high above retail prices, making shallot farmers want fertilizer subsidies from the government even though the subsidies provided are still inadequate and uneven. The purpose of this study was to analyze the effect of providing fertilizer on land area, seed needs, and prediction of fertilizer needs for shallots. The results of this analysis resulted in the design of business processes in the supply of fertilizers using the Business Process Reengineering Life Cycle method. Primary data collection was carried out using questionnaires and interviews with shallot farmers. The results showed that the production of fertilizer needs in accordance with the area of land and the number of seeds used. Therefore, efforts to increase the competitiveness of shallots can be carried out by proposing the BPR Life Cycle, so that the proposed framework is expected to be realized in order to increase productivity and build farmer institutions to realize further agricultural development.